CALIBRATION CHAMBER TESTS OF THE CONE-PRESSUREMETER IN SAND - Schnaid, F; Houlsby, G (Thomas Telford, 1990)
A set of tests of the cone-pressuremeter in a large calibration chamber are described. The observed limit pressures, as well as the cone resistance values, are found to be related primarily to the in-situ horizontal stress and the density. The ratio of cone resistance to limit pressure is found to be primarily determined by the sand density. A procedure for deducing the in-situ horizontal stress and density from the results of the cone-pressuremeter tests is described, and is shown to give reasonable values when used to back-analyse the tests. -Authors